PENGARUH CASH TURNOVER (CTO), TOTAL ASSET TURNOVER (TATO) DAN DEBT TO ASSET RATIO ( DAR ) TERHADAP RETURN ON ASSET (ROA) PADA PT KALBE FARMA TBK PERIODE 2013-2022 - Arum Utami, Diah; Janudin (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of Cash Turnover (CTO), Total Asset Turnover (TATO) and Debt to Asset Ratio (DAR) on Return on Asset (ROA) at PT Kalbe Farma Tbk. Both partially and simultaneously. The method used is the Quantitative Method. With the sample used is the financial summary, financial position and profit and loss statements of PT. Kalbe Farma Tbk for the period 2013-2022. Data analysis using descriptive statistical tests, classical assumption tests, multiple regression analysis, hypothesis tests, and determination coefficient tests. The results of the partial test Cash Turnover has a negative but insignificant effect on Return on Asset with a significance value of 0.529> 0.05 and a t_count value of -0.668 <t_table 2.365. Total Asset Turnover has a positive and significant effect on Return on Asset with a significance value of 0.003 <0.05 and a t_count value of 4.750> t_table 2.365. Debt to Asset Ratio has a positive but insignificant effect on Return on Asset with a significance value of 0.527> 0.05 and a t_count of 0.671 <t_table 2.365. The results of simultaneous testing of Cash Turnover, Total Asset Turnover and Debt to Asset Ratio have a positive and significant effect on Return on Asset with a significance value of 0.000 <0.05 and F_count 42.622> F_table 4.760. The results of the Determination Coefficient test show an Adjusted R-Square of 0.933, meaning that the influence of Cash Turnover, Total Asset Turnover and Debt to Asset Ratio on Return on Assets together has a contribution of 89.95%. Meanwhile, 10.5% is influenced by other variables not analyzed in this study.